Genetic mapping of host resistance to soybean sudden death syndrome. Issue 2 (2nd February 2022) - Collins, Paul Joseph; Tan, Ruijuan; Wen, Zixiang; Boyse, John F.; Chilvers, Martin I.; Wang, Dechun
Abstract: Soybean sudden death syndrome (SDS) is a disease caused by a soil‐borne fungus, Fusarium virguliforme . Many genetic studies have attempted to identify genes responsible for the quantitative host resistance to SDS. Three recombinant inbred line (RIL) populations were evaluated for foliar SDS resistance at a naturally infested field site in Decatur, MI, during the 2014 and 2015 growing seasons. Lines were evaluated for disease severity (DS) on a 1–9 scale, disease incidence (DI) as an estimate of the percentage of plants with symptoms per plot, and disease index (DX) as a metric which integrates DS and DI. Phenotypic data was spatially adjusted to account for uneven pathogen distribution in the naturally infested field. A subset of RILs from each population were genotyped with the SoySNP6K Illumina Infinium BeadChip. Linkage maps unique to each population were constructed using JoinMap ver. 2. Composite interval mapping was performed using WinQTLCartographer ver. 2.5. Three quantitative trait loci (QTL) were identified across 2 yr and/or multiple populations. One QTL on Chromosome 10 appeared to be colocalized with the E2 maturity locus. Another QTL identified was on Chromosome 18, in a region which has been demonstrated to provide soybean cyst nematode (SCN) and SDS resistance in many studies (rhg1/Rfs2). Core Ideas: The results confirmed the identification of a major host resistance quantitative trait loci on Chromosome Gm18. This quantitative trait loci has also been identified as a region which has resistance to soybean cyst nematode. The results suggest a connection between sudden death syndrome and soybean cyst nematode.